2010
DOI: 10.3346/jkms.2010.25.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics of Mucinous Carcinoma of the Breast in Korea: Comparison with Invasive Ductal Carcinoma-Not Otherwise Specified

Abstract: Clinicopathological characteristics and prognostic factors of mucinous carcinoma (MC) were compared with invasive ductal carcinoma-not otherwise specified (IDC-NOS). Clinicopathological characteristics and survivals of 104 MC patients were retrospectively reviewed and compared with those of 3,936 IDC-NOS. The median age at diagnosis was 45 yr in MC and 47 yr in IDC-NOS, respectively. The sensitivity of mammography and sonography for pure MC were 76.5% and 94.7%, respectively. MC showed favorable characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
7
22
0
1
Order By: Relevance
“…[9] Accordingly, 1.7% of our patients had MBC, consistent with the published data. This disease generally affects the elderly individuals, with <1% of the patients being <35 years of age.…”
Section: Discussionsupporting
confidence: 81%
“…[9] Accordingly, 1.7% of our patients had MBC, consistent with the published data. This disease generally affects the elderly individuals, with <1% of the patients being <35 years of age.…”
Section: Discussionsupporting
confidence: 81%
“…MC also has a higher rate of oestrogen receptor (ER) expression (73-94% versus 26-82%, supplementary material, Figure S5) and is associated with more progesterone receptor (PR) expression (63-90% versus 47-74%, supplementary material, Figure S6) [137][138][139][140][146][147][148][149][150][151]. For MC, less HER-2 overexpression has been reported compared with NMC (0-14% versus 20-41%, supplementary material, Figure S7) [139,140,146,147,[149][150][151]. Studies that included small numbers of MC demonstrated that mutated PIK3CA, which is found in 16-33% of IDCs, is not a common finding in MC (0-13%), supplementary material, Figure S8 [125,[152][153][154][155][156][157].…”
Section: Mucinous Breast Carcinomamentioning
confidence: 99%
“…MC of the breast is associated with higher rates of MUC2 expression than IDC [98,145]. MC also has a higher rate of oestrogen receptor (ER) expression (73-94% versus 26-82%, supplementary material, Figure S5) and is associated with more progesterone receptor (PR) expression (63-90% versus 47-74%, supplementary material, Figure S6) [137][138][139][140][146][147][148][149][150][151]. For MC, less HER-2 overexpression has been reported compared with NMC (0-14% versus 20-41%, supplementary material, Figure S7) [139,140,146,147,[149][150][151].…”
Section: Mucinous Breast Carcinomamentioning
confidence: 99%
“…The majority of previous MBC clinical studies found that MBC showed higher ER-and PR-positive rates, less lymph node metastasis, lower TNM stage and notably higher OS and DFS rates (16)(17)(18)(19)(20). The present study analyzed the basic information of MBC patients and compared it with that from IDC-NOS patients treated in the same period.…”
Section: Discussionmentioning
confidence: 99%